2019
DOI: 10.15406/ijfcm.2019.03.00146
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in Mozambique; a systematic review

Abstract: Context: Neuro-psychiatric disorders are the world's highest cause of incapacity. Mental disease in Africa is taboo and stigmatized, making it a challenge of a silent even hidden epidemy. In Sub-Saharan Africa it is estimated that 20% of patients with mental disorders are treated in primary health care centres and 50-75% are not detected in health facilities. In Mozambique, the prevalence of mental disorders and the frequency with which mental patients are treated at health facilities are not known. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Currently, there is a paucity of empirical literature on psychosocial distress among in-school adolescents in Mozambique. This is essential because a study has identified children and adolescents in Mozambique as the cohort with high odds of mental disorders, including psychosocial distress [20]. Due to this, the present study examined the prevalence and correlates of psychosocial distress among adolescents in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a paucity of empirical literature on psychosocial distress among in-school adolescents in Mozambique. This is essential because a study has identified children and adolescents in Mozambique as the cohort with high odds of mental disorders, including psychosocial distress [20]. Due to this, the present study examined the prevalence and correlates of psychosocial distress among adolescents in Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…We found that men had a more than six-fold increased odds of substance use and dependence compared with women (aOR = 0.16), which is corroborated by previous research that found that men present a burden of disorders related to the consumption of alcohol and drugs almost six times greater than women. [32][33][34] We also found that HIV-positive serostatus was associated with an almost six-fold increased odds of substance misuse and dependence compared with those who reported being HIV negative (aOR = 0.17). HIV-positive status has a well-established association with substance use and dependence, both inside 35 and outside 36 of primary care settings, and integrated primary care models have sought to address this frequent co-occurrence.…”
Section: Discussionmentioning
confidence: 80%
“…As for African Countries with Portuguese as an Official Language (PALOP), there is a scarcity of studies on the influence of these positive factors on mental health and suicidal behavior. Among existing literature, a review from Pires et al (2019) concluded that the Mozambiquan population shows a high burden of mental illness due to the lack of conventional health services and cultural adaptation of therapies.…”
Section: Positive Factors In Cplcmentioning
confidence: 99%